Penggunaan Nirmana-Komposisi Tak Berbentuk Sebagai Dasar Pembuatan Pola Surface Design - Marina Wardaya (Universitas Multimedia Nusantara, 2021)
The Nirmana course is a compulsory basic course for students studying design or fine arts. Nirmana teaches elements and elements contained in images, designs and the beauty of art in classifying elements and elements in order to create a work of art that is good and has meaning, therefore creating an aesthetic value. Art and aesthetics are a unity between elements that have harmony, harmony and balance. Beauty is an abstract concept that cannot be enjoyed because it is not clear but can communicate and make it fun to look at. Nirmana is a core that is implemented in the manufacture of each design as well as works of art, namely some important rules and must be used. The purpose of this study is to see the implementation of nirmana's courses in ready-to-wear media. The method used is a literature review and a descriptive, exploratory analysis approach. Keywords: nirmana; surface design pattern; basic education; design